Detection of lard and randomized lard as adulterants in refined-bleached-deodorized palm oil by differential scanning calorimetry - Marikkar, Mohammed Nazrim; Lai, O.M.; Ghazali , H.M.; Che Man , Y.B. (Springer Berlin, 2001)
A study was conducted to assess the use of differential scanning calorimetry (DSC) for detecting the presence of lard/randomized lard as adulterants in refined bleached deodorized (RBD) palm oil. Lard extracted from the adipose tissues of pig was chemically interesterified using sodium methoxide as catalyst. DSC thermal profiles of both genuine lard and randomized lard were compared with those of other common animal fats such as beef tallow, mutton tallow and chicken fat. DSC analyses of RBD palm oil blended separately with genuine and randomized lard in proportions ranging from 0.2 % to 20% lard were also obtained. The DSC cooling profiles of adulterated RBD palm oil samples showed an adulteration peak corresponding to lard/randomized lard in the low temperature region. This peak was confirmed as an indicator of the presence of lard in RBD palm oil since similar experiments carried out using other common animal fats such as mutton tallow, beef tallow and chicken fat showed that the lard adulteration peak could be distinctly identified. Using this method, a detection limit of 1% lard/randomized lard was reached (p < 0.0001).